2016
DOI: 10.1088/1612-2011/13/3/035402
|View full text |Cite
|
Sign up to set email alerts
|

Random laser action in stoichiometric Nd3Ga5O12garnet crystal powder

Abstract: This work explores the room temperature infrared random laser (RL) performance of Nd3+ ions in a new stoichiometric Nd3Ga5O12 crystal powder. The time-resolved measurements show that the RL pulse is able to follow the subnanosecond oscillations of the pump pulse profile. The pump threshold energy and the absolute stimulated emission energy have been measured using a method developed by the authors. The laser slope efficiency is the highest compared to other Nd3+ stoichiometric RL crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…We have observed that, in Nd stoichiometric crystal powders with a similar grain size, this delay time is much shorter [34,35]. In regular laser systems, this delay time between pump intensity and emission fluctuations is determined by the residence time of the photon inside the resonator [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed that, in Nd stoichiometric crystal powders with a similar grain size, this delay time is much shorter [34,35]. In regular laser systems, this delay time between pump intensity and emission fluctuations is determined by the residence time of the photon inside the resonator [36].…”
Section: Resultsmentioning
confidence: 99%
“…The slope efficiency in the Nd:YAG crystal powder is lower than those of Nd in stoichiometric crystal powders with a similar grain size, which can achieve a value close to a 40% due to their higher absorbance peaks [33,35]. It is important to remark that this value of the slope efficiency means that every absorbed photon above the threshold energy is reemitted again as a stimulated emission photon.…”
Section: Resultsmentioning
confidence: 99%
“…Using a fiber‐coupled random laser, where the pump fiber terminates deep inside the scattering medium in order to deliver the pump energy directly into the gain volume without reflection loss at the surface, Noginov et al achieved a higher efficiency of ≈0.7% . Azkargorta et al achieved 20% and 42% slope efficiencies with respect to pump power using Nd: yttrium aluminium garnet (YAG) and Nd 3 Ga 5 O 12 crystal powders …”
Section: Introductionmentioning
confidence: 99%
“…As the RL experiments show [12,29,32,33], far enough above threshold, the output/input energy function asymptotically tends to a line of slope one. As can be seen in Fig.…”
Section: Results From the Numerical Model In The Energy Domainmentioning
confidence: 94%
“…In Fig. 4 we show the experimental energy output/input of a Neodymium Gallate [29,32,33] together with the results of our simulation using different values of p and σ. The optimal fit is obtained for values of p slightly lower than 0.1 and the stimulated emission cross-section is not very sensitive to changes in p. Figure 5 shows the theoretical fitting for a Neodymium Borate [29,32,34].…”
Section: Results From the Numerical Model In The Energy Domainmentioning
confidence: 99%